Platinum nanoparticles in photothermal therapy of cancer cells - Aswad, Dunya Sarmad; Qoqaj, Iliriana (UCPH NanoScience - a student research journal, 2018)
Noble nanoparticles are potential photothermal therapy agents, due to their properties, such as ability to modify particle surface chemistry, and efficient light-to-heat conversion. In this work, we study the possible application of platinum nanoparticles as agents in photothermal therapy, their uptake, and toxicological response in the human ovarian cancer cell line (SK-OV-3) by flow cytometry. No oxidative stress, or toxicological response of the platinum nanoparticles was observed in the cells. Laser irradiation revealed photothermal destruction of SK-OV-3 cells exposed to 70 nm platinum nanoparticles at power density 45 W/cm2 after 5 minutes using an 808 near infrared laser.